Cell therapy for severe burn wound healing. Issue 1 (28th May 2018) - Li, Zhe; Maitz, Peter
Abstract: Cell therapy has emerged as an important component of life-saving procedures in treating burns. Over past decades, advances in stem cells and regenerative medicine have offered exciting opportunities of developing cell-based alternatives and demonstrated the potential and feasibility of various stem cells for burn wound healing. However, there are still scientific and technical issues that should be resolved to facilitate the full potential of the cellular devices. More evidence from large, randomly controlled trials is also needed to understand the clinical impact of cell therapy in burns. This article aims to provide an up-to-date review of the research development and clinical applications of cell therapies in burn wound healing and skin regeneration.